HYPERTENSION PHENOTYPES, TARGET ORGAN DAMAGE AND STIFF ARTERIES AND SEVERITY OF COVID-19. (April 2021) - Mahmud, Azra; Alhabdan, Nawaf Abdulaziz; Alkhdiri, Mohammad Hamad; Alahaideb, Ruba; Rajendrum, Rajkumar
Abstract : Objective: Since the Coronavirus Disease 2019 (COVID-19) pandemic began, conflicting reports have emerged regarding its association with hypertension (HTN) in various populations worldwide. However, there is paucity of data regarding the association between the severity of COVID-19 and HTN phenotypes and HTN mediated organ damage (HMOD). Design and method: In a cohort of patients (n = 501, mean age 53.5 ± 14.6) attending a specialist hypertension clinic at King Abdulaziz Cardiac Center, Riyadh, Saudi Arabia, we identified patients diagnosed with COVID-19 between January and November, 2020. We compared HTN phenotypes and HMOD in patients admitted with severe COVID-19 infection to those with mild disease and without disease. Data were analysed using JMP version 13 Pro (SAS for Windows). Results: Twenty-seven patients developed COVID-19 (5.38%), 8 of whom were admitted (29.6%), with one fatality (3.8%). Patients admitted with COVID-19 were more likely to have refractory HTN (43% vs. 15% vs. 8.9%, p < 0.01), body mass index > 30 (85.7% vs. 46% vs. 47%, p < 0.05), left ventricular hypertrophy (28.6% vs. 7.7% vs. 6.5%, p < 0.01), high hs-CRP (7.8 ± 1.1 vs. 2.1 ± 2 vs. 5 ± 1.5, p < 0.01) and greater central systolic pressure (132 ± 5 vs. 122 ± 7 vs. 110 ± 13, p < 0.01) with no difference in age and gender. Conclusions: In hypertensive patients, severe COVID-19 is associated with severe uncontrolled hypertension with HMOD and stiff arteries. While this is a small single center study, it does highlight aspects of COVID-19 in hypertensive patients which warrant further investigation.